(untitled) (American Journal of Islam and Society, 1998)
Let us begin with the challenge of a definition. What is globulizution? It consists of processes that lead toward global interdependence and the increasing rapidity of exchange across vast distances. The word globulizution is itself quite new, but the actual processes toward global interdependence and exchange started centuries ago. Four forces have been major engines of globalization across time: religion, technology, economy, and empire. These have not necessarily acted separately, but often have reinforced each other. For example, the globalization of Christianity started with the conversion of Emperor Constantine I of Rome in 3 13. The religious conversion of an emperor started the process under which Christianity became the dominant religion not only of Europe but also of many other societies thousands of miles distant from where the religion started. The globalization of Islam began not with converting a ready-made empire, but with building an empire almost from scratch. The Umayyads and Abbasids put together bits of other people’s empires (e.g., former Byzantine Egypt and former Zoroastrian Persia) and created a whole new civilization. Voyages of exploration were another major stage in the process of globalization. Vasco da Gama and Christopher Columbus opened up a ...